Reinventing Government Ekowisata Kabupaten Jember: Reinventing Government Ecotourism in Jember Regency - Ahmad Fadli (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2016)
Regional autonomy has causally opened opportunities for reorienting the local governance system to improve. A system that transcends the norms of a bureaucratic-oriented system by providing the greatest opportunity for regions to manage their areas according to the ideals, aspirations, and hopes of society, with a focus on maximizing public service. This policy is interpreted as a policy derived from local potential and dedicated to the progress and prosperity of the region, capable of serving the community well, enhancing welfare, and ensuring societal tranquility. Implikasi otonomi daerah secara kausalitas telah membuka peluang reorientasi sistem tata kelola pemerintahan daerah untuk menjadi lebih baik. Sebuah sistem yang melampaui normativitas sistem birokratis dengan memberikan peluang sebesar-besarnya kepada daerah untuk mengelola wilayahnya sesuai dengan idealitas, cita-cita, dan harapan masyarakat dalam orientasi maksimalisasi pelayanan publik. Kebijakan ini diartikan sebagai kebijakan yang bersumber dari potensi lokal dan ditujukan untuk kemajuan serta kemakmuran daerah, serta mampu melayani masyarakat dengan baik, meningkatkan kesejahteraan, dan menciptakan ketentraman.